a)
[tex]f(x)=\frac{(x^3-2x^2+x)(x+1)^2}{x^2-1}[/tex]
Dziedzina:
[tex]x^2-1\neq 0\\(x-1)(x+1)\neq 0\\x\neq 1\land x\neq -1\\D_f=\mathbb{R}-\{-1,1\}[/tex]
Miejsca zerowe:
[tex]\frac{(x^3-2x^2+x)(x+1)^2}{x^2-1}=0\ |*(x^2-1)\\(x^3-2x^2+x)(x+1)^2=0\\x(x^2-2x+1)(x+1)^2=0\\x(x-1)^2(x+1)^2=0\\x_1=0\\x_2=1\notin D_f\\x_3=-1\notin D_f[/tex]
Ostatecznie:
[tex]x_0=0[/tex]
b)
[tex]f(x)=\frac{1-(x+3)^2}{(x+2)^2}[/tex]
Dziedzina:
[tex](x+2)^2\neq 0\\x+2\neq 0\\x\neq -2\\D_f=\mathbb{R}-\{-2\}[/tex]
Miejsca zerowe:
[tex]\frac{1-(x+3)^2}{(x+2)^2}=0\ |*(x+2)^2\\1-(x+3)^2=0\\(1-x-3)(1+x+3)=0\\(-x-2)(x+4)=0\\x_1=-2\notin D_f\\x_2=-4[/tex]
Ostatecznie:
[tex]x_0=-4[/tex]